Determination of Risk Factors in Children Diagnosed With Henoch-Schönlein Purpura - Beltinge DEMİRCİOĞLU KILIÇ and Belde KASAP DEMİR (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the frequency of skin, gastrointestinal, joint, and renal involvement in children with Henoch-Schönlein purpura and investigate the risk factors for organ/system involvement. Patients and methods: The data of 186 patients (97 boys, 89 girls; mean age 7.4±2.8 years; range 1.5 to 16.5 years) who were followed-up with the diagnosis of Henoch-Schönlein purpura in our clinic between October 2011 and December 2013 were evaluated retrospectively. Results: Logistic regression analysis revealed that the risk of gastrointestinal system involvement was significantly higher in patients with skin lesions in the upper extremities (p=0.002, odds ratio [OR]=3.2). The risk of joint involvement was significantly higher in girls (p=0.024, OR=2.18), in patients with soft tissue swelling (p=0.005, OR=2.63), and with low mean platelet volume levels (p=0.008, OR=4.07). The risk of renal involvement was significantly higher in girls (p=0.047, OR=2.7), in patients >10 years (p=0.001, OR=1.4), and in patients with elevated C-reactive protein levels (p=0.007, OR=6.57). Conclusion: Having skin lesions in the upper extremities is a risk factor for gastrointestinal system involvement. Female sex, soft tissue swelling, and low mean platelet volume levels are risk factors for joint involvement. Female sex, >10 years of age, and high C-reactive protein levels are risk factors for renal involvement. Renal involvement in Henoch-Schönlein purpura is independent of gastrointestinal system or joint involvement and very close follow-up is required in the acute period particularly in girls >10 years with high C-reactive protein levels.